Water Requirements for Drip-Irrigated Tomato Production in Southwest Florida - Craig D. Stanley; G. A. Clark (EDIS)
Water management in drip irrigated tomato production requires information about the water needs of the crop as well as the water holding characteristics of the soil. Excessive irrigation can leach crop nutrients from the root zone while soil moisture deficit can result in crop stress. This publication will briefly present estimates of tomato plant water requirements under drip irrigated conditions for crops produced in the southwest Florida region. This is document SL-213, a publication of the Soil and Water Science Department, Florida Cooperative Extension Service, IFAS, University of Florida. Published February 2004.